A novel HLA‐B*38 variant, B*38:15, detected in a Taiwanese individual. (25th July 2016) - Yang, K. L.; Hung, J. H.; Lin, P. Y.
Abstract : One nucleotide substitution at residue 346 of HLA‐B*38:02:01 results in a novel allele, HLA‐B*38:15 .